Penentuan Jumlah dan Jenis Monorail Jalur Kampung Melayu-Roxy pada Berbagai Skenario Jumlah Penumpang Menggunakan Simulasi ProModel Berdasarkan Biaya yang Terbaik - Mirna Lusiani (Universitas Bunda Mulia, 2017)
Determination Types and Number of Trains Kampung Melayu-Roxy Monorail With Level Number Of Passengers Distribution Scenario Using Promodel Simulation Based On The Optimal Cost. Monorail is one of the solution to solve the traffic problem in the city of Jakarta. This project developed to be an alternative of mass public transportation service for the citizens in Jakarta. In order to be able to serve the passengers during peak time, the project need to have a research in term of the optimal total number of trains and type to be used. In this research, had chose the types and the total number of trains Kampung Melayu-Roxy with the level number of passengers distribution scenario based on the optimal cost using simulation. Scenario for the number of passengers per hour based on peak hour. Data gathered from variety sources such as consultant, suppliers, and media. Data required to developed a model, based on the observation of the Busway corridor Blok M-Kota. After developed the model, the next step is to simulated each type on each passengers distribution scenario to obtained the total number of trains and the headway. Selection based on incremental internal rate of return between two type on each scenario. Based on simulation and calculation result obtained that small type is the type of monorail that had been chose for monorail project at Kampung Melayu-Roxy line on several number of passengers scenario, with the description are scenario 1 with 10 units, scenario 2 with 14 units, scenario 3 with 15 units, and scenario 4 with 20 units.